Chronic Rhinosinusitis with Nasal Polyps and Biologics: A Call for Better Data Standardisation and Presentation in Clinical Studies - Kariyawasam HH; Langan D; Rimmer J (Therapeutics and Clinical Risk Management)
Harsha Hemantha Kariyawasam,1,2 Dean Langan,3 Joanne Rimmer4– 6 1Specialist Allergy and Clinical Immunology, Royal National ENT Hospital, London, UK; 2Rhinology Section, Royal National ENT Hospital, London, UK; 3Great Ormond Street Institute of Child Health, UCL, London, UK; 4Department of Otolaryngology Head & Neck Surgery, Monash Health, Melbourne, Australia; 5Department of Surgery, Monash University, Melbourne, Australia; 6Department of Otolaryngology Head & Neck Surgery, St Vincent’s Hospital, Melbourne, AustraliaCorrespondence: Harsha Hemantha Kariyawasam, Specialist Allergy and Clinical Immunology, Rhinology Section, Royal National ENT Hospital London and UCLH NHS Foundation Trust, 47-49 huntley Street, London, WC1E 6DG, UK, Email harsha.kariyawasam@nhs.netAbstract: Chronic rhinosinusitis with nasal polyps (CRSwNP) is often severe, debilitating and difficult to treat. Recent randomised control trials (RCTs) of biologics that target key inflammatory pathways have demonstrated clinical efficacy in treating CRSwNP. Such RCTs must facilitate meta-analysis. Here we report the need for urgent improvement in double-blind randomised controlled trials of biologics in CRSwNP, having previously undertaken a systematic review and meta-analysis of such studies. The RCTs included in that systematic review did not conform to a standard study design. Patient selection criteria was not consistent in studies with several heterogeneous disease subgroups of CRSwNP patients present in each study. Different durations of treatment and variable outcome measures also made the comparative assessment of efficacy between different biologics difficult. Data presentation to allow extraction for meta-analysis was not always clear, such that on occasion selected data sets or even an entire RCT had to be excluded from further evaluation. As such, the high heterogeneity between studies made the overall interpretation of the findings difficult. We make an urgent call to design and conduct future RCTS of biologics in CRSwNP in a more standardised manner, and to present data in a clear way that is easily extractable. This will facilitate more inclusive and thus robust evaluation and interpretation via meta-analysis, which will in turn enable clearer insight into which CRSwNP patient subgroups might benefit from specific biologics and thus achieve better clinical outcomes.Plain Language Summary: Future randomised clinical trials should be performed in a more standardised manner, ensuring each trial team collects the same type of clinical information and outcome data at the required timepoints. All such trials should report the data in an easy-to-understand way. This will allow better meta-analysis interpretation of data.Primary researchers should aim to present summary statistics relating to outcomes separately for each arm of their project. This should also be reported separately at each evaluation timepoint.For numeric outcomes, this should include the mean, standard deviation and the number of observations that the summary is based on. For binary outcomes, the number of individuals experiencing the event should be reported alongside the number of observations that the summary is based on.Effect estimates and inferential statistics presented in a journal article are less ideal for meta-analysis. However, if researchers do choose this option, then estimates should be accompanied by a standard error or confidence interval. P-values can also be presented at the discretion of the researchers, but this does not best facilitate meta-analysis.Primary researchers should generally facilitate meta-analysis by presenting results in a flexible way that allows reviewers to change the type of effect measure (eg, to derive an odds ratio or a relative risk).Primary researchers should ensure that the corresponding author of the paper is available for questions via email.Keywords: biologics, nasal polyps, clinical trials, outcomes, standardisation